He Loves the One He Has Invested In: The Effects of Mating Cues on Men’s and Women’s Sunk Cost Bias - Chen, Rui; Sun, Hao; Guo, Zhaoyang; Chen, Haipeng (Allan) (Journal of Consumer Research, 2025)
Abstract The sunk cost bias, that is, people’s suboptimal tendency to continue to pursue previously invested options, has been found in many domains, and various mechanisms have been proposed. The current study offers a novel perspective for understanding sunk cost bias. Drawing on previous findings suggesting that sunk cost bias may be adaptive and promoted by fundamental motives, it is theorized that sunk cost bias may be a goal-oriented behavior in the mating domain and that this bias can extend to consumption domains (e.g., product/service with nonrefundable deposits, lotteries earned through prior effort, loyalty program memberships obtained through previous purchases) when mating cues are salient. One field study and seven experiments (six of which were pre-registered) demonstrated that mating cues strengthen an implemental mindset among men (vs. women). Consequently, men exhibit a stronger sunk cost bias in consumption when mating cues are salient. However, this effect was not found among women due to differences in their mating tactics. In addition, this article distinguishes sunk cost effect from status quo bias and rules out multiple alternative explanations for the results (including affect, overconfidence, the investment-payoff link, persistence, perceived morality, shame, guilt, and disgust associated with abandoning the original option).